Economic policy supporting social well-being. Remarks on the margin of Ludwig Erhard’s book “Prosperity for All” - Marcin Łuszczyk (Rozwój Regionalny i Polityka Regionalna)
The purpose of the article is to present the achievements of Ludwig Erhard in the field of economic policy and his vision of social well-being. Immediately after World War II, Erhard was the main author of Germany’s economic policy. Based on the principles of ordoliberalism, the social market economy became the source of economic success.